Model analysis of worm gear pair system using finite element analysis - Barshikar, Raghavendra; Baviskar, Prasad; Patil, Milind M.; Dube, Anil S.; Dhore, Vishal J. (Zielona Góra: Uniwersytet Zielonogórski)
Spur gear, helical gear, worm gear, and bevel gear are all important components in industrial applications such as vehicles, pushes, conveyors, elevators, bowl mill, rolling mills, ribbon blender, machine tools, aeroplanes, and windmills. When various types of defects, such as wear, tooth breakage, corrosion, and scratches on bearings, appear in gearboxes, normal machine function may be abruptly terminated.
Keywords: worm gear pair; finite element analysis; model analysis; deformation; natural frequency